Evaluation of Pathogenicity of Entomopathogenic Oomycetes Lagenidium giganteum and L. ajelloi against Anopheles Mosquito Larvae - Mathew Mumo Sila; Fredrick Mutie Musila; Vitalis Wafula Wekesa; Imbahale Susan Sangilu (Psyche: A Journal of Entomology)
Malaria is a mosquito-borne life-threatening parasitic disease of humans and the leading cause of mortality and morbidity in sub-Saharan Africa. Despite the major efforts made towards malaria control, it is facing challenges of development of parasite resistance towards antimalarial drugs coupled with Anopheles vector resistance towards insecticides being used in control. There is, therefore, a need to develop complementary control strategies that are economical and environmentally friendly. Biological control using entomopathogenic fungi against the immature malaria mosquito vectors presents an untapped opportunity. This study sought to isolate and characterize entomopathogenic oomycetes Lagenidium giganteum and L. ajelloi from wild Anopheles larvae from Ahero rice fields in western Kenya and test their pathogenicity against laboratory-reared Anopheles gambiae larvae. Laboratory-reared A. gambiae larvae (3rd and 4th instar) were exposed to five different concentrations of L. giganteum and L. ajelloi zoospores; 1000, 2000, 3000, 4000, and 5000 zoospores/mL, respectively. The larval mortality was recorded after 24, 48, 72, and 96 hours post-exposure, until all larvae were dead. The results obtained showed that L. giganteum was not pathogenic to A. gambiae larvae after 24 and 48 hours post-exposure to all concentrations. Larval mortality was recorded at 72 and 96 hours. There were no significant differences observed in the mortalities p>0.05 from all treatments. No mortalities were observed in deionized water (negative control) whereas 100% mortality was recorded in larvae exposed to Bti (positive control). Probit analysis showed that LC50 after 72 hours and 96 hours was 2.32 × 104 and 3.51 × 103 zoospores/ml, respectively. L. ajelloi caused larval mortalities at all the 5 test concentrations after 24-, 48-, 72- and 96-hours post-exposure with LC50 values of 1.18 × 105, 1.43 × 104, and 6.05 × 102, and 27.08 zoospores/ml, respectively. This study isolated and tested two species of Lagenidium from field collected larvae. Lagenidium ajelloi recorded greater pathogenicity than that of L. giganteum against A. gambiae larvae, making them potential candidates for use in the development of bio-larvicide for the control of Anopheles larvae.